Divided in schools, divided in society: challanges of schooling in a post-conflict community - Čorkalo Biruški, Dinka (Array, 2011)
The panel disscussed challanges of education in postconflict divided societies. Experts from the region and abroad shared their experiences in organizing formal and informal approaches to education for children and youth living in post-conflict environment. Formal schooling but also other forms of brining youth together, like summer camps, workshops, seminars, educative trips, youth conferences etc. were identified as powerful tools for establishing contacts and closer relations among children who belong to different ethnic groups. In this way education was acknowledged as an important step in bringing about social change.